Digital transformation at what cost? A case study from Germany estimating the adoption potential of precision farming technologies under different scenarios - Johannes Munz; Ines Maurmann; Heinrich Schuele; Reiner Doluschitz (Smart Agricultural Technology)
This study addresses the research gap in understanding the low adoption of Precision Agriculture Technologies (PATs) by extrapolating regional trends from in-depth farm-level analyses. Focusing on a smallholder region in Germany, it investigates the adoption limits of PATs, questioning whether the low rates are due to unknown economic thresholds and how these thresholds can be influenced. Six PATs are evaluated, along with the impact of six potential measures to increase adoption rates, using predictive economic modeling and scenario analysis. Findings confirm low adoption rates, peaking at 4.61 % for automatic guidance and 17.73 % for site-specific fertilization, highlighting that current strategies are only partially effective, especially for precision weeding, site-specific seeding, planting, and spraying. Fortunately, targeted interventions for less adopted PATs enhance average farm income, which may increase their broader acceptance. The study advocates for targeted, technology-specific strategies over broad measures like subsidies, emphasizing the effectiveness of private sector initiatives like machinery cooperatives and service providers in improving adoption. The study concludes that greater PAT uptake in agriculture is only possible if realistic expectations are set by all stakeholders and tailored strategies are developed to promote a comprehensive digital transformation of the sector.